Green synthesis of colloidal silver nanoparticles by sonochemical method - Huang, N.M.; Darroudi, M.; Khorsand Zak, A.; Muhamad, M.R.; Hakimi, M. (2012)
A facile sonochemical method was developed for preparing colloidal silver nanoparticles (Ag-NPs) in aqueous gelatin solutions. The effect of the reducing agent and Ag + concentrations, ultrasonic time, and ultrasonic amplitude on the particle size has been investigated. The size of the Ag-NPs decreases with the ultrasonic amplitude and increases with ultrasonic time. Well-dispersed spherical Ag-NPs with a mean particle size of about 3.5 nm have been synthesized under ultrasonic process. The use of gelatin as an eco-friendly stabilizer provides green and economic attributes to this work. This preparation method is general and may be extended to other noble metals, such as Au, Pd and Pt, and may possibly find various additional medicinal, industrial and technological applications. Â© 2011 Elsevier B.V.